Integrative Model of Digital Literacy and Online Platforms to Promote the Economic Resilience of Small-Scale Fishermen in West Sulawesi Province - Ernawaty mappigau; Femiliani Novitasari; Andi Nursiskawaty; Adi Zulkarnaen; Suharlina Suharlina (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2026)
Small-scale fishermen face structural challenges such as limited market access, fluctuations in catch prices, and low technological and information capacity. This study aims to analyze the level of digital literacy, the use of online platforms, and their impact on the economic resilience of small-scale fishermen in West Sulawesi, as well as to design an integrative model to strengthen digital capabilities and market access. The method used is a mixed-methods approach involving a survey of 150 fishermen, in-depth interviews, and focus group discussions (FGDs). Quantitative data were analyzed using descriptive statistics and multiple linear regression, while qualitative data were analyzed thematically. The research results indicate that fishermen’s digital literacy remains low to moderate, the utilization of fisheries marketplaces is relatively low, and digital literacy and access to online platforms have not yet significantly impacted fishermen’s economic resilience due to infrastructure limitations, high data plan costs, insufficient guidance, and the dominance of traditional transactions. The study proposes an integrative model that combines the improvement of digital literacy based on fishermen’s needs, the utilization of simple online platforms, and sustainable institutional support to strengthen fishermen’s bargaining power and expand market access.